Learning from Brazil’s dengue outbreak for Mumbai’s monsoon preparedness: a public health perspective - C. S., Ramalakshmi; Shah, Anuradha Kunal; Chavan, Yuvaraj B.; K., Vignesh (International Journal Of Community Medicine And Public Health, 2026)
The expansion of dengue fever is a growing concern globally, with over half a million cases and more than 100 deaths reported worldwide as of January 2024. Dengue is now present in 85% of Brazil’s municipalities, spreading into regions where it was never seen before. The aim and objective of the study is to look into the dengue outbreak in Brazil searching for contributing factors and to compare the presence of similar factors in Mumbai region. The study involves comprehensive review of existing literature about Brazil outbreak in online. Attempting to search for articles based on relevance to dengue fever cases and its management in Brazil and potential implication for Mumbai. Conclusion were drawn from expert opinion. The expansion of dengue fever is a growing concern globally, with over half a million cases and more than 100 deaths reported worldwide as of January 2024. Dengue is now present in 85% of Brazil’s municipalities, spreading into regions where it was never seen before. The aim and objective of the study is to look into the dengue outbreak in Brazil searching for contributing factors and to compare the presence of similar factors in Mumbai region. The study involves comprehensive review of existing literature about Brazil outbreak in online. Attempting to search for articles based on relevance to dengue fever cases and its management in Brazil and potential implication for Mumbai. Conclusion were drawn from expert opinion. Brazil’s situation is dire, with over 1 million cases reported early this year 2024 and projections suggesting up to 4.2 million cases by year’s end. But, between January to April 2024, 5.9 million of dengue cases reported. Due to the onset of El Nino and also due to extreme weather, untimely rainfall, flooding, stagnant water pools which leads to thriving of mosquito and prolongation of active transmission period. Steps were taken to reduce the Dengue outbreak. By prediction as per El Nino cyclicity, there will be no surge of dengue cases in Mumbai. But, in sprit of staying prepare and not to caught unaware, Mumbai is making precaution for dealing with dengue outbreak.with over 1 million cases reported early this year 2024 and projections suggesting up to 4.2 million cases by year’s end. But, between January to April 2024, 5.9 million of dengue cases reported. Due to the onset of El Nino and also due to extreme weather, untimely rainfall, flooding, stagnant water pools which leads to thriving of mosquito and prolongation of active transmission period. Steps were taken to reduce the Dengue outbreak. By prediction as per El Nino cyclicity, there will be no surge of dengue cases in Mumbai. But, in sprit of staying prepare and not to caught unaware, Mumbai is making precaution for dealing with dengue outbreak.